Some medical applications of the oxford scanning proton microprobe. - Vaux, D; Grime, G; Watt, F (1987)
Results from several medical investigations carried out using the Oxford scanning proton microprobe are presented, including maps of the hepatic copper-distribution in primary biliary cirrhosis and maps of the iron distribution in primary hemochromatosis. Preliminary studies of human nervous tissue reveal that morphologically recognizable structures can be differentiated using precision elemental mapping, and this may lead to a powerful new way of distinguishing subtle perturbations of structure and function. In further prelimianry studies, localized aluminum structures have been observed in Alzheimer's disease tissue at bulk levels of less than parts per million.